HOW DOES AN AUDITOR'S REPUTATION AFFECT GOVERNANCE AND FINANCIAL FRAUD IN INDONESIAN STATE-OWNED ENTERPRISES? - Widya Apriana Rahayu; Novia Widyastuti; Annisa Salsabila Safanah; Riyan Harbi Valdiansyah (Jurnal Akuntansi dan Keuangan, 2024)
This study explores how governance mechanisms affect financial statement fraud and the moderating influence of auditor reputation using moderated regression analysis on a sample of 72 Indonesian Stock Exchange-listed companies from 2019 to 2021. The commissioner boards significantly reduce financial statement fraud, whereas the audit committee's effect is insignificant. When moderated by audit quality, the commissioner boards significantly impact financial statement fraud, whereas audits have an insignificant effect on audit reputation moderation. This study provides insights for SOE top management on the effectiveness of governance mechanisms in preventing financial statement manipulation and enhances understanding of how these mechanisms, aligned with government legitimacy, can mitigate agency conflicts between SOE management and stakeholders. Future studies could investigate additional factors beyond corporate governance mechanisms or employ different criteria for measuring independent variables to obtain more comprehensive results.